Bengal Provincial Conference, 1906, Barisal Session - Ghosh, Yatindrakumar (Ghosh : distributors, Firma KLM, 1978)
Comprises proceedings of a concention and newspaper reportage of a nationalist organization of Bengal during the Indian freedom movement.